Impact of timing of delivery on maternal and neonatal outcomes for women after three previous caesarean deliveries; a secondary analysis of the caesarean section registry. (25th March 2019) - Breslin, N; Vander Haar, E; Friedman, AM; Duffy, C; Gyamfi‐Bannerman, C
Abstract : Background: As more women are presenting with three previous caesarean deliveries (CD), providers may suggest early term delivery as a means to avoid the risk of spontaneous labour and associated maternal morbidity. Objective: To determine whether early term delivery is associated with lower maternal and neonatal morbidity for women with three previous CD. Study design: Secondary analysis of a prospective registry of CD at 19 US academic centres from 1999 to 2002. Population: Women with three previous CD undergoing scheduled or emergent delivery with live, singleton gestations 37–41+ weeks of gestation were included. Women with non‐low transverse incisions, antepartum stillbirth, previous myomectomy, fetal anomalies, more or fewer than three previous CD or attempting trial of labour after caesarean section were excluded. Methods: Gestational age was categorised by week. We fitted logistic regression models to adjust for clinically relevant or statistically significant confounders. Main outcome measures: The primary and secondary outcomes were composites, respectively, of maternal and neonatal morbidity. Results: In all, 821 women met the inclusion criteria; maternal morbidity composite occurred in 9.86% and neonatal morbidity occurred in 10.5%. After adjusting for confounding variables, maternal and neonatal morbidity occurred least frequently at 39 weeks. Conclusions: In women with three previous CDs, adverse maternal outcomes do not increase with increasing gestational age beyond 37 weeks but early term elective repeat CDs are associated with higher neonatal morbidity. Elective delivery of women with three previous CD at 39 weeks of gestation is safe in the absence of maternal or fetal indications for early term delivery. Tweetable abstract: Delivery of women with three previous caesarean deliveries at 39 weeks, in the absence of maternal or fetal indications for early term delivery, is associated with decreased maternal morbidity. Abstract : Tweetable abstract Delivery of women with three previous caesarean deliveries at 39 weeks, in the absence of maternal or fetal indications for early term delivery, is associated with decreased maternal morbidity.